Positive Selection during Niche Adaptation Results in Large-Scale and Irreversible Rearrangement of Chromosomal Gene Order in Bacteria. (28th March 2022) - Cao, Sha; Brandis, Gerrit; Huseby, Douglas L.; Hughes, Diarmaid
Abstract: Analysis of bacterial genomes shows that, whereas diverse species share many genes in common, their linear order on the chromosome is often not conserved. Whereas rearrangements in gene order could occur by genetic drift, an alternative hypothesis is rearrangement driven by positive selection during niche adaptation (SNAP). Here, we provide the first experimental support for the SNAP hypothesis. We evolved Salmonella to adapt to growth on malate as the sole carbon source and followed the evolutionary trajectories. The initial adaptation to growth in the new environment involved the duplication of 1.66 Mb, corresponding to one-third of the Salmonella chromosome. This duplication is selected to increase the copy number of a single gene, dctA, involved in the uptake of malate. Continuing selection led to the rapid loss or mutation of duplicate genes from either copy of the duplicated region. After 2000 generations, only 31% of the originally duplicated genes remained intact and the gene order within the Salmonella chromosome has been significantly and irreversibly altered. These results experientially validate predictions made by the SNAP hypothesis and show that SNAP can be a strong driving force for rearrangements in chromosomal gene order.